Guidance and Counseling Management in Schools: A Systematic Literature Review of Models, Result and Challenges - Syapitri, Denia; S, Neviyarni (International Journal of Applied Counseling and Social Sciences, 2025)
Guidance and counseling (GC) management in schools is a crucial component in ensuring effective services for students. However, empirical studies related to its management models, outcomes, and challenges are still scattered and not systematically integrated. This study aims to systematically review the literature on GC management in schools. The method used was a systematic literature review with reference to the PRISMA guidelines. Article searches were conducted through the Scopus database with the support of the WataseUake.id platform for the period 2015-2025. Of the 607 identified articles, a step-by-step screening process resulted in seven articles that met the inclusion criteria and were further analyzed. The results of the study indicate that GC management is evolving towards a comprehensive and systems-based approach, such as the Comprehensive School Counseling Program and the ASCA National Model, which has a positive impact on service effectiveness and counselor professionalism, despite still facing limited resources and policy support.